Phǣn phatthanā sām pī Phō̜.Sō̜. 2552-2554 Thētsabān Nakhō̜n Nakhō̜n Sawan (Ngān Wikhro̜ Nayōbāi læ Phǣn, Fāi Phǣnngān læ Ngoppramān, Kō̜ng Wichākān læ Phǣnngān, Thētsabān Nakhō̜n Nakhō̜n Sawan, 2008)
Three-year development plan, 2009-2011, of Muang District Municipality, Nakhon Sawan Province, upper Central Thailand.